Usulan Perbaikan Manajemen Risiko Untuk Penerapan Program K3 - Hetharia, Monica Myline; Yuamita, Ferida (Universitas Bojonegoro, 2023)
Risk management in the Occupational Health and Safety (K3) program provides a safe working environment essential to protecting employees. To improve the effectiveness of K3 risk management, the study proposes improvements using Hazard Identification and Risk Assessment methods. (HIRA). The study aims to identify potential hazards and evaluate the risks associated with hot work in the work environment. Using the Hazard Identification and Risk Assessment (HIRA) approach, risks can be identified more effectively and enable companies to take appropriate action to improve the effectiveness of risk management in occupational health and safety programs. (K3). The research methods used include document analysis, field observations, interviews, and surveys. The collected data will be analyzed using HIRA methods that include identifying hazards, assessing risks, and making recommendations for appropriate risk control. The results of this research are expected to enhance our understanding of the potential hazards and risks associated with the workplace. The resulting improvement recommendations will help the company implement appropriate precautions and improve K3 risk management.